Cognitive impairment and academic performance in students with sensorineural hearing loss in Kongo Central, Democratic Republic of the Congo - Pholo Manzimbala , Jean Paul; Kilara , Tarcisse; Lema, Gabriel; Kalala , Hilaire; Kandala, Bienvenue; Matanda, Richard; Sokolo, Jérôme; Mbambu, Eddy Mampuya (Orapuh Journal, 2025)
IntroductionSeveral studies in the literature have highlighted the impact of cognitive impairment and academic performance (AP) in students with sensorineural hearing loss in specialised schools for the deaf. However, few studies have been conducted on this subject in our setting.PurposeThe objective of this study was to determine the influence of hearing impairment (HI) and cognitive level on AP in students attending specialised schools for the deaf in Kongo Central.MethodsThis was a cross-sectional study conducted among 126 deaf students. The parameters collected included sociodemographic, clinical, and paraclinical data. HI was confirmed using pure tone audiometry (PTA) and classified according to WHO criteria. Cognition was assessed using Raven’s Standard Progressive Matrices (SPM), a non-verbal intelligence test, to determine the intelligence quotient (IQ). Data were analysed using SPSS version 26.0.ResultsA total of 126 students, including 75 boys, were enrolled. The dominant age group was >18 years (44.4%). Most participants were Jehovah’s Witnesses (38.1%) and lived in low-income households (62.7%). Nearly 85.7% of the students had severe to profound HI, with post-lingual onset in 60.3%, and 57.1% had a low IQ. The mean AP was 50.54 ± 6.56%. There was a weak negative correlation between hearing loss and AP (r = -0.30; p < 0.001). Students with above-average IQ had significantly higher AP scores compared to those with low or average IQ (p = 0.005). A significant negative correlation was also observed between advancing age and IQ (p < 0.001), indicating that IQ tends to decline slightly with age, explaining 10.7% of the variance.ConclusionThe lack of schooling for deaf children is a significant issue in our context. Advancing age significantly impairs AP, underscoring the need to enrol these students at the appropriate school age.